Overview of skin whitening agents with an insight into the illegal cosmetic market in Europe. (8th March 2016) - Desmedt, B.; Courselle, P.; De Beer, J.O.; Rogiers, V.; Grosber, M.; Deconinck, E.; De Paepe, K.
Abstract: Lightening skin tone is an ancient and well‐documented practice, and remains common practice among many cultures. Whitening agents such as corticosteroids, tretinoin and hydroquinone are medically applied to effectively lighten the skin tone of hyperpigmented lesions. However, when these agents are used cosmetically, they are associated with a variety of side‐effect. Alternative agents, such as arbutin and its derivatives kojic acid and nicotinamide have been subsequently developed for cosmetic purposes. Unfortunately, some cosmetics contain whitening agents that are banned for use in cosmetic products. This article provides an overview of the mode of action and potential side‐effects of cosmetic legal and illegal whitening agents, and the pattern of use of these types of products. Finally, an EU analysis of the health problems due to the presence of illegal products on the market is summarized.